Destination Branding Indramayu Untuk Meningkatkan Daya Saing dan Kepercayaan Publik - Purnamasari, Oktaviana; Munawaroh , Azizatul; Hariyati, Farida; Saputri, Sabrina Zulfanova (Education and Talent Development Center of Indonesia, 2025)
Indramayu, situated on the northern coast of Java, is a region rich in natural resources, as well as significant tourism and local cultural potential. Indramayu's distinctive batik, often referred to as Batik Paoman, along with culinary delights such as pindang gombyang, nasi lengko, mango dodol, and kue koci, are highly appealing tourist attractions that warrant greater promotion. Unfortunately, much of this potential remains underdeveloped, thus failing to significantly boost the local economy. Consequently, from 2020 to 2023, Indramayu became one of Indonesia's largest senders of migrant workers. This can be attributed to the insufficient empowerment of local communities to establish businesses, leading them to seek employment abroad. To elevate Indramayu's tourism and local cultural potential, a destination branding campaign is essential. Through destination branding, Indramayu's tourism potential can be effectively communicated and leveraged as a unique strength to differentiate it from other regions, thereby attracting both local and international tourists. This initiative has the potential to enhance Indramayu's competitiveness and public trust. This community service program aims to educate local press journalists, who serve as the vanguard of online mass media reporting, about destination branding. Journalists received dedicated sessions covering the intricacies of destination branding and best practices for Indramayu, which they subsequently reported on in online media. There was also a practical